Manipulation of Auditory Inputs as Rehabilitation Therapy for Maladaptive Auditory Cortical Reorganization - Hidehiko Okamoto (Neural Plasticity)
Neurophysiological and neuroimaging data suggest that the brains of not only children but also adults are reorganized based on sensory inputs and behaviors. Plastic changes in the brain are generally beneficial; however, maladaptive cortical reorganization in the auditory cortex may lead to hearing disorders such as tinnitus and hyperacusis. Recent studies attempted to noninvasively visualize pathological neural activity in the living human brain and reverse maladaptive cortical reorganization by the suitable manipulation of auditory inputs in order to alleviate detrimental auditory symptoms. The effects of the manipulation of auditory inputs on maladaptively reorganized brain were reviewed herein. The findings obtained indicate that rehabilitation therapy based on the manipulation of auditory inputs is an effective and safe approach for hearing disorders. The appropriate manipulation of sensory inputs guided by the visualization of pathological brain activities using recent neuroimaging techniques may contribute to the establishment of new clinical applications for affected individuals.